PENGARUH NAUNGAN TERHADAP PERTUMBUHAN DAN LAJU FOTOSINTESIS TANAMAN CABE MERAH (Capsicum annuum L) SEBAGAI SALAH SATU SUMBER BELAJAR BIOLOGI - Mustofa Khoiri (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
This research aim to know the effect of wings of to growth and photosynthesis speed at red pepper crop. The result of the research indicates that wings of to red pepper crop from aspect morfologis haves an in with plant height and plane flattened dry weight, but at leaf wide, leaves, and effect leaf length wings of doesn't significan influence compared with control. From physiological aspect, wings of at red pepper crop influences value quantum yield, photochemical quenching, and non photochemical quenching, but at value Q max doesn't show real influence. In aspect ecophyisiologic, wings of triggering produce of prolin and ascorbic acid which significan. Inferential that red pepper Capsicum annuum L very responsive in process of adaptation to environmental change for example grasp in the form of low light intensity. The result of the research gives contribution as source of teaching material in biology learning. Kata kunci: Naungan, Capsicum annuum L, aspek ekofisiologis.